Hope in a Jar : The Making of America's Beauty Culture - Peiss, Kathy Lee (Book collections on Project MUSE., 2011)
In Hope in a Jar, historian Kathy Peiss gives us the first full-scale social history of America's beauty culture, from the buttermilk and rice powder recommended by Victorian recipe books to the mass-produced products of our contemporary consumer age. She shows how women, far from being pawns and victims, used makeup to declare their freedom, identity, and sexual allure as they flocked to enter public life. And she highlights the leading role of white and black women-Helena Rubenstein and Annie Turnbo Malone, Elizabeth Arden and Madame C.J. Walker-in shaping a unique industry that relied less on advertising than on women's customs of visiting and conversation. Replete with the voices and experiences of ordinary women, Hope in a Jar is a richly textured account of the ways women created the cosmetics industry and cosmetics created the modern woman.